Resistance Against Patriarchy In The Poor Things Film by Yorgos Lanthimos - Ariffa, Putri Ramadaniah (English Literature Department, Adab and Humanities Faculty, 2025)
Patriarchy is a social system that places men as dominant and women as subordinate, both in the private and public spheres. This research aims to analyze the forms and effects of patriarchy, and resistance toward patriarchy in Yorgos Lanthimos' film Poor Things. The approach used is a feminism approach with a qualitative descriptive method. This research used Sylvia Walby's theory (1991) to describe the forms of patriarchy and explain the effects of patriarchy. The researcher explained resistance to patriarchy used Simone De Beauvoir's theory (2014). The results of the research show that 1) there are two forms of patriarchy namely private patriarchy and public patriarchy. 2) There are four effects of patriarchy: gender equality, oppression of women, marginalization, and unequal decision making 3) There are three ways to resist patriarchy done by main female character: becoming economically independent, joining and involving social community, and improving the quality of education. The portrayed life of women under control in this film becomes a form of criticism against male dominance, particularly within the household. Through the representation of the patriarchal system, this film is expected to raise public awareness of gender inequality issues that still frequently occur around us.